Perception of the services and disservices from urban forest and trees in the Garden City of West Africa - Patrick Opoku; Eric Kwame Simpeh; Henry Mensah; Dorothy Asare Akoto; Norbert Weber (Trees, Forests and People, 2024)
The growth of trees in urban areas brings forth an extensive array of services and disservices, the comprehension of which can assist urban forestry professionals in advancing a more sustainable urban forest ecosystem. This paper assesses the perception of urban residents on the services and disservices from urban trees in a less represented geographic area. Using a mixed method approach, primary data was gathered from 396 urban inhabitants in the study area. Exploratory factor analysis was used to assess perception of services and disservices from the urban trees. Using a principal component analysis, it was found out that the most important services provided by urban trees were health and climate improvement as well as energy, esthetic and environmental benefits. These services explained 50.8% of citizens’ perception variance and are linked to basic human needs. Additionally, the Monte Carlo parallel analysis-based on exploratory factor analysis revealed that the underlying problems that needs to be addressed were related to poor management and maintenance of urban trees, destruction of infrastructure by trees and issues related to safety including parks and gardens serving as hideouts for criminals in the city. These components were predicting 53.3% of the problems and disservices of urban trees. The results provide a valuable insight for urban forestry professionals. The findings imply that institutional assistance should be increased, and the legislative structure changed to address these challenges to sustain urban forestry.